Governance Collaboration in Local Public Service Innovation: A Qualitative Study Using NVivo Analysis in District-Level Government Institutions - Muliati; Jumria (Meraja journal, 2025)
[Full Paper] to pdf Copyright (c) 2025 Meraja journal